Olean (1,7-dioxaspiro[5.5]undecane): A Novel Intraspecific Chemical Cue in Coraebus undatus (F.) (Coleoptera: Buprestidae) - Sergio López; José María Álvarez-Calero; Josep Maria Riba-Flinch; María Milagro Coca-Abia; Antoni Torrell; Carmen Quero (Insects, 2021)
The main aim of this work was to identify semiochemicals from the jewel beetle Coraebus undatus (F.) (Coleoptera: Buprestidae) that may aid in the improvement of current monitoring tools. First, HS-SPME collections revealed that individually sampled adults (>7 days old) of both sexes release the spiroacetal 1,7-dioxaspiro[5.5]undecane (olean). Electroantennographic recordings from both sexes exposed to increasing amounts of olean followed a dose-dependent pattern, with females being more responsive than males to the highest amount of the compound (100 µg). In double-choice assays, adults older than seven days were significantly attracted to olean, whereas this attraction was not detected in insects aged less than seven days. Indeed, a repellent effect was observed in young females. Subsequent field trials employing sticky purple prism traps revealed that there were no differences among the number of insects caught in control and olean-baited traps at two different release rates (0.75 and 3.75 mg/day). Interestingly, all the trapped specimens were determined as mated females, regardless of the presence of olean. Overall, these findings provide a basis for unraveling the chemical ecology of the species, although further research is still needed to determine the specific role of this compound within the chemical communication of the species.